Organization of services for mental health : mental health policy and service guidance package. (World Health Organization, 2003)
Mental health services make it possible to deliver effective interventions. The way these services are organized has an important bearing on their effectiveness and the ultimate fulfilment of the aims and objectives of national mental health policies. This module begins with a description and analysis of the current forms of mental health service organisation found around the world. The current status of service organisation is reviewed and recommendations are made for organising mental health services, based on an optimal mix of a variety of services. The main recommendations are to integrate.